Facile Synthesis of In Situ Graphitic-N Doped Porous Carbon Derived from Ginkgo Leaf for Fast Capacitive Deionization. Issue 8 (30th April 2019) - Xie, Zhengzheng; Shang, Xiaohong; Xu, Kaibing; Yang, Jianmao; Hu, Bin; Nie, Pengfei; Jiang, Wenwen; Liu, Jianyun
Abstract : The ginkgo leaf-derived graphitic-N-doped porous carbon was fabricated by one-step carbonization in the presence of KOH agent. The morphology, surface functional groups, element state and porous structure of the obtained carbon were investigated systematically. Compared with the carbon samples by ginkgo-leaf carbonization and KOH post-activation (two-step), the one-step activated porous carbon exhibits high graphitic-N content and good electric conductivity. The conductive-agent-free carbon sheet was made successfully and the resultant carbon electrode possesses good conductivity and excellent electrochemical properties, with the specific capacitance of 176.1 F g −1 . When being applied for capacitive deionization, the desalination amount of the electrode arrived at 16.5 mg g −1 . Meanwhile, the salt adsorption rate is very rapid, with the average salt adsorption rate reaching 1.5 mg g −1  min −1 . This work provides an easy and environmentally benign route for the synthesis of the conductive carbon from natural raw materials for highly efficient capacitive deionization.